An Agri-Food Supply Chain Model to Enhance the Business Skills of Small-Scale Farmers Using Corporate Social Responsibility - Sutopo, Wahyudi; Hisjam, Muh.; Yuniaristanto, Yuniaristanto (Makara Journal of Technology, 2012)
In general, small-scale vegetable farmers experience problems in improving the safety and quality of vegetables for supplying high-class consumers in modern retailers. Farmer Group and/or Cooperative (FGC) should be able to assist its members to meet the relevant provisions of modern retail on product specifications, delivery terms, and internal business requirements. This study proposed an agri-food supply chain (ASC) model that involves the corporate social responsibility (CSR) activities to enhance the business skills of the FGC as supplier of modern retailer. Multi-objective optimization programming is developed to determine the amount and timing of supply, level of farmers training skills, quality improvement target, and the CSR total cost. The results show that the proposed model can be used to determine the priority of programs in order to empower farmers' groups as modern retail suppliers.